The iconicity and learnability of selected picture communication symbols : a study on Afrikaans-speaking children - Basson, Hester Magdalena (2013)
Everyday communication occurs mostly through speech, thus learners who have little or no functional speech (LNFS) need to augment their communication by using additional communication strategies to ensure that they are able to participate in the interaction process. The use of Augmentative and Alternative Communication (AAC) can and should play an important role in assisting learners with LNFS to access information and services and to communicate. Graphic symbols form an important part of most AAC users’ communication systems. Therefore studies which focus on increasing understanding of the way different graphic symbols are learnt and retained by children and adults, are pivotal for a better understanding of the processes involved in graphic symbol learning. Iconicity and learnability of symbols are two important factors to consider when choosing an appropriate graphic symbol set/system. The purpose of the current study was to determine how accurately typically developing urban, 6-year-old Afrikaans-speaking children could firstly, identify 16 PCS presented thematically on a commercially available communication overlay, and secondly, recognize these symbols following exposure to a learning experience. Forty-six participants, divided into 2 cohorts, were each presented with 16 copies of a 16-matrix overlay and required to match a symbol with a spoken Afrikaans label. The participants were then divided into two groups, one group receiving training in the meaning of the symbols and the other group receiving no training. Finally the test-procedure was repeated with the cohorts. The results indicated that the 16 PCS symbols had an iconicity of between 12.5 % (accuracy score > 50 %) and 25 % (accuracy score > 75 %) for the combined group. Results further indicated a significant improvement in both the experimental and the control groups’ post-test results. The significant difference between the two groups’ post-test results does, however, indicate that the experimental group recognized more symbols during the post-test administration than the control group and they had thus benefited from the training session. The control group’s better post-test results can be attributed to the single exposure through the pre-test procedure. The participants made use of the information afforded them by the postural cues implying motion. They did not, however, make full use of the arrow cues or the direction of the arrows, which also implied motion. Once the participants of the experimental group were made aware of the arrows, they seemed to use the information the arrows offered to help them remember the symbol meanings during the post-test procedure. Copyright 2004, University of Pretoria. All rights reserved. The copyright in this work vests in the University of Pretoria. No part of this work may be reproduced or transmitted in any form or by any means, without the prior written permission of the University of Pretoria. Please cite as follows: Basson, HM 2004, The iconicity and learnability of selected picture communication symbols : a study on Afrikaans-speaking children, MA dissertation, University of Pretoria, Pretoria, viewed yymmdd < http://upetd.up.ac.za/thesis/available/etd-10042005-155306/ > === Dissertation (M (Alternative and Augmentative Communication))--University of Pretoria, 2006. === Centre for Augmentative and Alternative Communication === unrestricted